Inventory Of Termite Species In The Area Of Islam Riau University And Efficiency Of Fungus Metarhiziumanisopliae Against Terms In The Laboratory - Inggit Piandari; saripah ulpah; T. Edy Sabli; Salmita Salman (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Termites have a great potential to cause damage to plants and other woody materials because these insects live in colonies. Termites' preferences and potential for harm vary depending on the species. Surveys related to termite species, estimates of damage that occurred, as well as preferences of plants and woody trees attacked in the Riau Islamic University Area were carried out as an initial step to avoid the impact of a greater termite attack. The survey results showed that termites were found in 9 of the 25 plots observed, namely Fisipol (3), Law (3), PKM Building (1), FKIP B (1), Mosque (1), Agriculture (3), Experimental Gardens (2), Student Dormitory (14), and Postgraduate (4). The types of termites that attack the Riau Islamic University area were obtained as many as four different termite species, namely Microcerotermes sp. (Family: Termitidae), Macrotermes sp. (Family: Termitidae), Schedorhinotermes sp (Family: Rhinotermitidae), and Coptotermes curvignathus (Family: Rhinotermitidae). Captotermes is one of the main pests in the Riau Islamic University area because it has been known to attack several plants for a long time. Laboratory tests using the fungus Metarhizium anisopliae showed the potential to cause mortality in termites at a spore density of 1.65 x 108 with a spore viability of 82.8%, resulting in a death time of 1.65 x 108. The best was 1.50 days and the mortality percentage was 99.17%. The spore density of Metarhizium anisopliae added with 10% zeolite was 3.5 x 107 with 90.3% spore viability (M2) resulting in a death time of 2.50 days and a mortality percentage of 75. .12%. Meanwhile, without treatment, the time of death was 5.25 days and the mortality percentage was 20.00%.